Crystal structure of vanadinite: Refinement of anisotropic displacement parameters - Laufek,F.; Skala,R.; Haloda,J.; Cisarova,I. (Journal of the Czech Geological Society, 2006)
The structure of vanadinite, Pb5(VO4)3Cl, from Mibladen, Morocco, was refined from single-crystal X-ray data. The full anisotropic structural refinement was carried out in the hexagonal space group P63/m, unit cell parameters a = 10.2990(2), c = 7.3080(1) A Å, V = 671.30(2) AÅ 3, Z = 2, with an R factor of 0.0197. The full anisotropic crystal structure refinement results in smaller departures of bond valence sums for cations from the ideal value than the isotropic one.
Keywords: Vanadinite; crystal structure; anisotropic displacement parameter; single-crystal X-ray refinement